Organophotoredox‐Catalyzed Switchable Selective Transformation of Aromatic Aldehydes into Pinacols and Benzyl alcohols. Issue 11 (25th October 2021) - Yedase, Girish Suresh; John, Maria; Yatham, Veera Reddy
Abstract: We report a versatile and efficient organophotoredox‐catalyzed (4CzIPN) chemo‐selective conversion of aromatic aldehydes and ketones into pinacols and benzyl alcohols. Hantzsch ester and thiophenol were used as the electron, proton and hydrogen atom donors. Product selectivity can be switched from pinacols to benzyl alcohols simply by adding a stoichiometric amount of thiophenol to the reaction system. The operationally simple protocol tolerates a variety of functional groups and selectively converts aromatic aldehyde into pinacol or benzyl alcohol in the presence of both aromatic ketone and aliphatic aldehyde. Abstract : A visible‐light‐driven, metal‐free catalyzed switchable chemo‐selective transformation of aromatic aldehydes and ketones into pinacols and benzyl alcohols is reported.